Dynamic in silico assessment of potential gene targets for enhancing clavulanic acid production in Streptomyces clavuligerus submerged cultures - David Gómez-Ríos, Howard Ramírez-Malule, Victor A. López-Agudelo (Journal of Applied Pharmaceutical Science, 2023)
Clavulanic acid (CA) is an antibiotic of the β-lactam class with moderate antimicrobial activity but a high inhibitory effect on β-lactamase enzymes. CA is one of the most important products of the secondary metabolism in Streptomyces clavuligerus, which is still the main industrial source of CA marketed worldwide. However, CA titers produced in submerged cultures by wild-type S. clavuligerus are characteristically low. The application of systems biology and constraint-based approaches such as the flux balance analysis (FBA) allows us to get insights into the metabolism, especially when it is coupled to a validated genome-scale model. In this study, FBA was applied for the in silico determination of potential metabolic targets aimed to increase the CA biosynthesis rate. In the metabolic network, the overexpression of N2-(2-carboxyethyl)-arginine synthase (CEAS), knockout of pyruvate kinase (PYK), and dampening of phosphoglycerate kinase showed the best flux ratio of CA biosynthesis. Then, submerged fed-batch cultivations with CEAS and PYK-engineered strains were simulated by using a dynamic FBA (dFBA) for analysis of the correspondent metabolic flux distribution. The dFBA provided insights about the carbon redistribution produced by the genetic perturbations potentially increasing CA production up to 1.9 and 1.1-fold for the calculated wild-type strain (2.74 mmol.l−1).